Towards a data-driven financial system: The impact of COVID-19 - REMOLINA LEON, Nydia (Institutional Knowledge at Singapore Management University, 2021)
The COVID-19 outbreak has a growing impact on the global economy and the financial sector, which plays a critical role in mitigating the unprecedented macroeconomic and financial shock caused by the pandemic. Given the unprecedented nature of the current crisis, financial regulators and supervisors, central banks, along with governments and legislatures face challenges to maintain financial stability, preserve the well-functioning core markets, and ensure the flow of credit to the real economy. Even though the COVID-19 has slowed down our daily lives and stopped the operation of many industries, it did not have the same effect in the data-driven finance world. The digital transformation of the financial services industry and financial technologies (fintech) have contributed to face some of the challenges of the pandemic. This paper explains the ongoing data revolution in the financial services industry and how traditional financial institutions and fintechs are trying to leverage data-driven solutions to respond to the challenges associated with the economic crisis derived from the pandemic. The paper also argues that despite the potential benefits of this transformation, the future of data-driven finance in a post-pandemic world looks challenging and generates many risks for consumers and the stability of the financial sector that regulators need to address. An adequate balance of different regulatory objectives will be crucial for a sustainable recovery in a post-pandemic financial industry.